SOSIALISASI LANGKAH PENCEGAHAN PENULARAN COVID-19 MELALUI PROGRAM KKN DI NAGARI LAGAN HILIR PUNGGASAN - Fuji Mayang Sari; Mahyudin Ritonga (Menara Pengabdian, 2021)
The spread of covid-19 is happening very quickly, while people in some areas are still doing activities such as normal atmosphere, therefore it takes efforts by various parties to share information with each other. In line with that, Real Work Lectures in the covid-19 period should be conducted on an during basis, students through supervisors are directed to implement programs that are in accordance with the urgent needs in the student's residential environment. In accordance with the direction of the implementation of the KKN, the community of Nagari Lagan Hilir Punggasan has less awareness of the dangers of covid-19 transmission, therefore the supervisor directs students to socialize covid-19 prevention measures to the community. The method of implementation is in the form of socialization by visiting places that are considered maximal to conduct socialization, in the success of the program designed, this activity also involves the kenagarian government. The result of the implementation of the service is that the community of Nagari Lagan Hilir Punggasan has an awareness about the importance of wearing masks, the community also has an awareness about the importance of washing hands at all times, and so do they have the awareness not to hold crowds during the covid-19 pandemic.